Pemberdayaan Pelaku UMKM melalui Model Edu Legal English untuk Penguatan Kesadaran Hukum dan Daya Saing Global - Neni Iryani; Lina Maulidiana (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2026)
Micro, small, and medium enterprise actors increasingly interact with digital marketplaces, electronic transactions, consumer data, branding, and cross-border communication. However, business assistance is often fragmented: legal education is delivered separately from practical English training, while English courses rarely address the actual legal and commercial communication needs of microentrepreneurs. This community service program introduced the Edu-Legal English model, an integrated empowerment approach combining contextual legal literacy, functional Business English, guided digital practice, and output-based mentoring for MSME actors in Cisauk Urban Village, Tangerang Regency. The activities used a participatory mentoring approach consisting of needs mapping, legal-risk identification, bilingual communication workshops, task-based practice, guided product profile development, and reflective evaluation. The program focused on business legality awareness, consumer protection, electronic transactions, trademarks, personal data, simple business documents, bilingual product descriptions, customer-response scripts, and basic negotiation expressions. The main outputs were a practical legal checklist, a Legal-English glossary, bilingual business profiles, bilingual product descriptions, and communication templates for digital marketplace interactions. Qualitative evaluation based on worksheets, completed business outputs, mentoring notes, and participant reflection indicated a shift from fragmented knowledge toward more integrated decision-making. Participants were better able to recognize legal risks in digital business communication and to produce simple English expressions that were more relevant to real selling situations. The program suggests that the Edu-Legal English model can serve as a contextual community empowerment framework that connects legal awareness with practical global communication readiness.